Healthcare-associated adverse events and readmission to the emergency departments within seven days after a first consultation - Gasperini, Guillaume; Bouazzi, Leila; Sanchez, Antoine; Marotte, Louis; Kézachian, Laury; Bellec, Guillaume; Cazes, Nicolas; Rosetti, Maxime; Bousquet, Claire; Renard, Aurélien; Sanchez, Stéphane (Frontiers in Public Health, 2023)
Introduction: The use of emergency medical services (EMS) has become increasingly frequent with a rise of approximately 3.6%. in annual emergency department (ED) visits. The objective of this study was to describe the reasons for reconsultations to EDs and to identify the risk and protective factors of reconsultations linked to healthcare-associated adverse events (AEs). Material and methods: A retrospective, descriptive, multicenter study was carried out in the ED of Troyes Hospital and the Sainte Anne Army Training Hospital in Toulon, France from January 1 to December 31, 2019. Patients over 18 years of age who returned to the ED for a reconsultation within seven days were included. Healthcare-associated AEs in the univariate analysis (p<0.10) were introduced into a multivariate logistic regression model. Model performance was examined using the Hosmer-Lemeshow test and calculated with c-statistic. Results: Weekend visits and performing radiology examinations were risk factors linked to healthcare associated AEs. Biological examinations and the opinion of a specialist were protective factors. Discussion: Numerous studies have reported that a first consultation occurring on a weekend is a reconsultation risk factor for healthcare-associated AEs, however, performing radiology examinations has been subject to confusion bias. Patients having radiology examinations due to trauma-related pathologies were more apt for a reconsultation. Conclusion: Our study supports the need for better ED access to biological examinations and specialist second medical opinions. An appropriate patient to doctor ratio in hospital ERs may be necessary at all times.